2010
DOI: 10.1186/1471-2474-11-38
|View full text |Cite
|
Sign up to set email alerts
|

Isolated talonavicular arthrodesis in patients with rheumatoid arthritis of the foot and tibialis posterior tendon dysfunction

Abstract: BackgroundThe foot is often affected in patients with rheumatoid arthritis. Subtalar joints are involved more frequently than ankle joints. Deformities of subtalar joints often lead to painful flatfoot and valgus deformity of the heel. Major contributors to the early development of foot deformities include talonavicular joint destruction and tibialis posterior tendon dysfunction, mainly due to its rupture.MethodsBetween 2002 and 2005 we performed isolated talonavicular arthrodesis in 26 patients; twenty women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 25 publications
1
25
0
4
Order By: Relevance
“…Satisfactory outcomes from screw arthrodesis, non-angle-stable plates and memory staples have been reported [5,20]. In a recent report, Jarrell et al [4] compared the biomechanical properties of screw versus combined plate-and-screw fixation for talonavicular fusion.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Satisfactory outcomes from screw arthrodesis, non-angle-stable plates and memory staples have been reported [5,20]. In a recent report, Jarrell et al [4] compared the biomechanical properties of screw versus combined plate-and-screw fixation for talonavicular fusion.…”
Section: Discussionmentioning
confidence: 96%
“…Chen et al reported adjacent joint arthritic changes occurred in 5 of 16 feet (31%) [11]. Popelka et al [5] recorded the progression of deformities and changes in surrounding joints in two patients (3 and 6 years after the operation). However, other authors have pointed out that, if the foot is placed in a well-aligned position, excessive stress and the development of adjacent arthritis can be minimized [27].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Review of the literature indicates that there are a large variety of osteosynthetic implants for the fusion of the talonavicular joint. Satisfactory outcome from screw arthrodesis [9], non angle-stable plates [10] and memory staples have been reported [11]. A recent report by Jarrell et al compared the biomechanical properties of screw versus combined plate and screw fixation for talonavicular fusion [12].…”
Section: Discussionmentioning
confidence: 97%